Combination vaccine based on citrullinated vimentin and enolase peptides induces potent CD4-mediated anti-tumor responses. Issue 1 (18th June 2020) - Brentville, Victoria A; Metheringham, Rachael L; Daniels, Ian; Atabani, Suha; Symonds, Peter; Cook, Katherine W; Vankemmelbeke, Mireille; Choudhury, Ruhul; Vaghela, Poonam; Gijon, Mohamed; Meiners, Ghislaine; Krebber, Willem-Jan; et al.
Abstract : Background: Stress-induced post-translational modifications occur during autophagy and can result in generation of new epitopes and immune recognition. One such modification is the conversion of arginine to citrulline by peptidylarginine deiminase enzymes. Methods: We used Human leukocyte antigen (HLA) transgenic mouse models to assess the immunogenicity of citrullinated peptide vaccine by cytokine Enzyme linked immunosorbant spot (ELISpot) assay. Vaccine efficacy was assessed in tumor therapy studies using HLA-matched B16 melanoma and ID8 ovarian models expressing either constitutive or interferon-gamma (IFNγ) inducible Major Histocompatibility Complex (MHC) class II (MHC-II) as represented by most human tumors. To determine the importance of CD4 T cells in tumor therapy, we analyzed the immune cell infiltrate into murine tumors using flow cytometry and performed therapy studies in the presence of CD4 and CD8 T cell depletion. We assessed the T cell repertoire to citrullinated peptides in ovarian cancer patients and healthy donors using flow cytometry. Results: The combination of citrullinated vimentin and enolase peptides (Modi-1) stimulated strong CD4 T cell responses in mice. Responses resulted in a potent anti-tumor therapy against established tumors and generated immunological memory which protected against tumor rechallenge. Depletion of CD4, but not CD8 T cells, abrogated the primary anti-tumor response as well as the memory response to tumor rechallenge. This was further reinforced by successful tumor regression being associated with an increase in tumor-infiltrating CD4 T cells and a reduction in tumor-associated myeloid suppressor cells. The anti-tumor response also relied on direct CD4 T cell recognition as only tumors expressing MHC-II were rejected. A comparison of different Toll-like receptor (TLR)-stimulating adjuvants showed that Modi-1 induced strong Th1 responses when combined with granulocyte-macrophage colony-stimulating factor (GMCSF), TLR9/TLR4, TLR9, TLR3, TLR1/2 and TLR7 agonists. Direct linkage of the TLR1/2 agonist to the peptides allowed the vaccine dose to be reduced by 10-fold to 100-fold without loss of anti-tumor activity. Furthermore, a CD4 Th1 response to the citrullinated peptides was seen in ovarian cancer patients. Conclusions: Modi-1 citrullinated peptide vaccine induces potent CD4-mediated anti-tumor responses in mouse models and a CD4 T cell repertoire is present in ovarian cancer patients to the citrullinated peptides suggesting that Modi-1 could be an effective vaccine for ovarian cancer patients.